(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background. PT.Centerpark in collaboration with Panakkukang Makassar Mall is a formal company engaged in providing parking services. Worker in this company wrork every day with an average of 8 hours a day, in a day worker is able to sit for 7 hours. So the risk of complaints pos ticket workers is very high. The purpose of this study was to determine the effect of using MSB on decrasing complaints of low back pain in the cash register cashiers at Panakkukang Mall Makassar in 2019. This study used pre and post tests to assess the level of low back pain in workers. Material and Method. The type of research used was an experimental quasi. The sampling method uses simple purposive sampling. The study was conducted in November - February 2020. The number of sampling was 30 people. The data analysis technique used in this study is Chi-square and Mann Whitney test. Results. The results showed that as The average level of low back pain before and after the use of MSB in the intervention group before using MSB the mean value is 4.93 mg/dl (SD = 1.03) after using MSB the mean value is 2.53 mg/dl (SD = 0.91). The use of MSB on the level of low back pain after treatment in the intervention group p (0,000) < p (0.05). The use of MSB on the level of low back pain after treatment in the control group was p (0,317) > p (0.05). There was a difference in changes in the scale of low back pain before and after using MSB in the intervention and control groups p (0,000) <p (0.05). Conclusion. There is a difference in the average level of the lower back before and after the use of MSB on the basis of the time before the use of MSB the average value of the worker level is 4.93 mg/dl (SD = 1.03) after using MSB 53 mg/dl (SD = 0.91). It is recommended for workers to use MSB tools every time they work.